To solve the expression \( 2 ( 1.6^0 + 7 ) - 4.9^0 \), we first need to evaluate the exponentials involving zero.
- Any non-zero number raised to the power of 0 is equal to 1. Therefore:
- \( 1.6^0 = 1 \)
- \( 4.9^0 = 1 \)
Now substituting these values back into the expression we have:
\[ 2 ( 1 + 7 ) - 1 \]
- Next, simplify inside the parentheses:
- \( 1 + 7 = 8 \)
So now our expression is:
\[ 2 ( 8 ) - 1 \]
-
Now, multiply:
- \( 2 \times 8 = 16 \)
-
Finally, subtract 1:
- \( 16 - 1 = 15 \)
Thus, the result of the expression \( 2 ( 1.6^0 + 7 ) - 4.9^0 \) is:
\[ \boxed{15} \]